Development of a production approach to build a titanium flaperon rib by directed energy deposition - Montero-Sistiaga, M.L.; Haagsma, R.L.; Osinga, T.; San Martin, U.; Smit, M.J. de; Nijhuis, P. (Springer, 2023)
Laser powder-directed energy deposition (LP-DED) is gaining interest in the production of complex large parts at a high production rate compared to conventional machining. Typically, these products are milled out of solid blocks. The aim of this work is to show the whole production chain to manufacture a titanium flaperon rib starting from the process optimisation to production and post-processing of the part itself. First, the process parameters for thin and bulky structures were optimised in LP-DED. Then different characteristic design features of the rib were defined and the manufacturing strategies were optimised. Lastly, all optimised strategies were applied for the production of the full-scale flaperon ribs. In this work, several design guidelines and optimum process conditions were obtained for Ti6Al4V processed by LP-DED. On one hand, the process parameters for thin walls and solid features were obtained. In addition, intersections and overhang structures were studied to achieve stable and high-quality connections. On the other hand, different strategies for reducing the deformations were studied and minimum deformations were obtained for large slender build plates. All developed strategies were implemented to successfully produce a large-sized flaperon rib in Ti6Al4V by powder LP-DED.